Fluimucil as a neuroprotective, is there anything new? Bibliometric study from 1996 to 2024 [version 1; peer review: awaiting peer review] - SALEH, ARMAN YURISALDI; Susanto, Tirta Darmawan; Valentina, Riezky; Saputra, Dwi Arwandi Yogi (F1000 research, 2025)
Introduction Fluimucil, also known as N-acetylcysteine (NAC), has been used as a medicinal drug for treating Alzheimer's and Parkinson's disease. Recent research has shown NAC's potential as a neuroprotective agent, preventing oxidative damage and promoting neurodegenerative treatment. This study conducted bibliometric analysis of articles related to NAC use, identifying research trends, current trends, and correlations between research and institutions. The findings can help identify unpublished research and guide future research strategies. This research not only provides public interest in NAC research but also offers valuable insights for future research. Methods In this work, a literature review methodology is employed to gather data from the Scopus database using the keywords fluimucil, nac, n-acetylcystein, and neuroprotective. Data were analyzed using Biblioshiny and VOSviewer software to produce visualizations and bibliometric maps. We conducted quantitative and qualitative analysis. Results The research trend found are Documents by Year, Documents by Author, Documents by Affiliations, Documents by country or territory, Documents by funding sponsor, Factorial Map Of The Documents With The Highest Contributes, Documents by Subject Area, Network Visualization, Overlay visualization of scopus database using Vosviewer, Density Visualization, Thematic Map, and Qualitative Analysis. Conclusions Research on the neuroprotective effects of N-acetylcysteine (NAC) or fluimucil has several limitations and strengths. It uses quantitative and qualitative analysis to identify research trends and mechanisms of NAC action. However, the data may be biased and the methodology may differ. The study has significant potential for future research, particularly in treating neurodegenerative diseases like Parkinson and Alzheimer. It also contributes to the understanding of NAC mechanisms.